Avian biochemistry and molecular biology - Stevens, Lewis (Cambridge University Press, 1996)
Egg laying, feather production and flight are energetically demanding, and birds have evolved distinct metabolic and genetic adaptations to cope. This book provides an up-to-date and comprehensive survey of both avian biochemistry and molecular biology for all researchers and postgraduate students with an interest in birds.